The Security Service of Ukraine’s counteraction to criminal offences at critical infrastructure facilities: organisational aspect - O. M. Herasymenko; D. S. Melnyk (Bulletin of Kharkiv National University of Internal Affairs)
The article is devoted to the theoretical foundations of organisation and management of the process of countering criminal offences by the Security Service of Ukraine at critical infrastructure facilities. Modern technological systems and their parts related to critical infrastructure facilities are subject to unlawful encroachments. The negative dynamics of the level of threats and losses from criminal attacks on these objects requires solving existing problems, and therefore consideration of issues related to solving existing problems becomes relevant for scientists.